The Economic Design of Sporting Contests - Szymanski, Stefan (Journal of Economic Literature, 2003)
This paper reviews the literature on commercial sport through the lens of the economic theory of contests/tournaments. It seeks to draw together research on incentives in individualistic sports such as golf and footraces with the research on uncertainty of outcome and competitive balance in team sports such as baseball and soccer. The contest framework is used to analyze issues such as the optimal distribution of prizes, the impact of revenue sharing, salary caps, draft rules, and a variety of other restraints commonly employed in sports leagues. The paper draws heavily on a comparative analysis of contest organization, in particular between North America and Europe.